Hubungan ketangguhan mental dan dukungan teman terhadap motivasi berprestasi atlet futsal putri - Noviansah, Indah; Fitri, Mustika; Hamidi, Ahmad; Apriady, Hilmy (Universitas Nusantara PGRI Kediri, 2025)
Despite the growing interest in the psychological factors influencing athletic performance, research on the interplay of MT, SS, and achievement motivation, specifically within the context of women's futsal, remains limited. This study explores the relationship between mental toughness, social support, and achievement motivation among female futsal athletes in Indonesia. This research gathered 18 female futsal athletes using the Multidimensional Scale of Perceived Social Support (MSPSS) and the Sports Mental Toughness Questionnaire (SMTQ) in a quantitative descriptive manner. The collected data will be analyzed using IBM SPSS Statistics version 25 software, with a focus on descriptive statistics, correlation, and linear regression analyses. The MSPSS evaluates perceived social support from sources like family and friends, while the SMTQ measures mental toughness, focusing on aspects such as self-confidence and resilience. The study results show that a correlation between MT and SS of 0.429 was found by statistical analysis; however, this association was not statistically significant (Sig. > 0.05). Descriptive analysis indicated that SS had a higher mean score (33.6403) compared to MT (31.2378), suggesting a higher perceived level of social support among participants. These findings highlight the need for further research to understand these dynamics comprehensively. This study contributes to understanding the psychological and social factors affecting the performance and well-being of female futsal athletes. It suggests the necessity for targeted interventions and support strategies.